2014
DOI: 10.1111/jocd.12086
|View full text |Cite
|
Sign up to set email alerts
|

Significant improvement in mild acne following a twice daily application for 6 weeks of an acidic cleansing product (pH 4)

Abstract: In this clinical trial, a topical cleansing product containing glycolic acid with pH 4 improved mild acne significantly following twice-daily application for 6 weeks as monotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
(41 reference statements)
1
10
0
Order By: Relevance
“…An emollient with a pH of 4.8 altered skin barrier and microbes in infants at risk for developing atopic dermatitis . Skin care products adjusted to pH 4 have been used successfully in acne skin . These products improve the physiological microbial flora, skin barrier and lipid lamellae structure, reduce skin dryness and have been described to be more favorable compared with formulations with a pH of 5.8–6.0 .…”
Section: Reducing Skin Ph As a Therapeutic Tool In Wound Healing Skimentioning
confidence: 99%
See 1 more Smart Citation
“…An emollient with a pH of 4.8 altered skin barrier and microbes in infants at risk for developing atopic dermatitis . Skin care products adjusted to pH 4 have been used successfully in acne skin . These products improve the physiological microbial flora, skin barrier and lipid lamellae structure, reduce skin dryness and have been described to be more favorable compared with formulations with a pH of 5.8–6.0 .…”
Section: Reducing Skin Ph As a Therapeutic Tool In Wound Healing Skimentioning
confidence: 99%
“…105 Skin care products adjusted to pH 4 have been used successfully in acne skin. 106 These products improve the physiological microbial flora, skin barrier and lipid lamellae structure, reduce skin dryness and have been described to be more favorable compared with formulations with a pH of 5.8-6.0. 97,[107][108][109][110] Newborn and aged skin exhibit an increased SC pH, too.…”
Section: Reducing Skin Ph As a Therapeutic Tool In Wound Healing Skimentioning
confidence: 99%
“…We previously reported that a face gel wash and a micellar solution containing mandelic acid reduced acne symptoms [13]. In addition, Abels et al reported that twicedaily application of a topical glycolic acid-containing cleansing product (pH 4) for 6 weeks led to a significant improvement of mild acne [14]. However, the patients in our previous study were treated with wash-out cosmetics in addition to cream containing azelaic acid and sodium salicylate.…”
Section: Discussionmentioning
confidence: 61%
“…Ali and Yosipovitch emphasize that the creation of acidic skin pH is essential for management of inflammatory dermatoses, while clinicians should focus on the selection of topical agents compatible with the skin . Prior work has documented the effectiveness of acidifying emollients in lowering pH of skin surface . However, all of the investigated formulations contained AHAs, while only few studies focused on their safety, or they used subjective methods of skin safety investigations which are normally considered unreliable .…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies show that SC acidification could be an effective strategy, even in management of the atopic march . Fortunately, SC acidification could normally be achieved by application of low pH topical formulations …”
Section: Introductionmentioning
confidence: 99%